Development of a natural nanostructured lipid carrier (NLC)-based delivery system as an antidiabetic and diabetic wound agent: A review - Novianti, Tamia Rizqi; Kusriani, R. Herni; Jafar, Garnadi (Science Midwifery, 2025)
Diabetes mellitus is a chronic metabolic disease characterized by hyperglycemia due to impaired insulin secretion. Diabetes often causes serious complications such as diabetic wounds, which are characterized by the appearance of ulcers, infections, or tissue damage in the feet. Conventional therapeutic approaches often show less than optimal effectiveness due to limited drug penetration into damaged skin tissue. The use of natural ingredients with antidiabetic and wound healing activities has been widely studied, but their effectiveness is often hampered by low solubility, stability, and bioavailability. One innovative strategy to overcome these problems is the development of nanotechnology-based drug delivery systems, one of which is Nanostructured Lipid Carrier (NLC). NLC is a lipid delivery system that combines solid and liquid lipids to increase stability, drug loading capacity, and control the release of active compounds. Purpose: This article aims to review the development of formulations from natural ingredients that have potential as antidiabetic and diabetic wound healing activities. Methods: This study is a literature review of articles published in the last ten years (2015 – 2025) from the ScienceDirect, PubMed, and Google Scholar databases. Results: Based on several studies, it shows that various active compounds such as curcumin (Curcuma longa), bay leaves (Syzygium polyanthum), and other flavonoid compounds have been formulated in the NLC system with significant improvements in stability, bioavailability, and pharmacological effectiveness. Conclusion: The NLC-based drug delivery system from natural ingredients has proven potential in increasing the effectiveness of antidiabetic therapy and diabetic wound healing. Further research is needed to optimize formulation stability, long-term toxicity testing, and clinical validation to support its therapeutic application.